Ubiquitin-mediated degradation at the Golgi apparatus - Buzuk, Lana; Hellerschmied, Doris (Frontiers in Molecular Biosciences, 2023)
The Golgi apparatus is an essential organelle of the secretory pathway in eukaryotic cells. It processes secretory and transmembrane proteins and orchestrates their transport to other endomembrane compartments or the plasma membrane. The Golgi apparatus thereby shapes the cell surface, controlling cell polarity, cell-cell communication, and immune signaling. The cytosolic face of the Golgi hosts and regulates signaling cascades, impacting most notably the DNA damage response and mitosis. These essential functions strongly depend on Golgi protein homeostasis and Golgi integrity. Golgi fragmentation and consequent malfunction is associated with neurodegenerative diseases and certain cancer types. Recent studies provide first insight into the critical role of ubiquitin signaling in maintaining Golgi integrity and in Golgi protein quality control. Similar to well described pathways at the endoplasmic reticulum, ubiquitin-dependent degradation of non-native proteins prevents the accumulation of toxic protein aggregates at the Golgi. Moreover, ubiquitination regulates Golgi structural rearrangements in response to cellular stress. Advances in elucidating ubiquitination and degradation events at the Golgi are starting to paint a picture of the molecular machinery underlying Golgi (protein) homeostasis.